Hydrogeological structure of shallow-buried coal seam in wind erosion landform area and water-retaining coal mining method - MENG Fanlin; LI Jiashan; SUN Zhihao; CAI Jin; QIAO Wei; WANG Qiqing; WU Huijie (矿业科学学报)
Xinjiang has an arid climate and scarce water resources, thus rendering the protection of water resources a major issue for coal mining. Taking the Yushuquan Coal Mine in Xinjiang as the study area, this study investigated the hydrogeological structure and water circulation patterns of the wind-eroded landform area and proposed the water-retaining coal mining method for the mine. Specifically, we first calculated the height of the water-conducting fracture zone of coal seam, based on which the direct water-filled aquifer of coal seam was determined and the water-rich zoning was conducted. We then analyzed the hydraulic connection between the water bodies in the mining area and the impact caused by mining based on the hydrological observation hole water level data in the study area. The aquifer on the roof of the coal seam and the aquifer in the burnt rock were determined as the target aquifers to be protected. Based on the degree of coal seam mining disturbance, we divided the study area into 3 regions and implemented corresponding water-retaining coal mining measures such as coal pillars retention and limited mining height, and accordingly proposed the reuse scheme of sewage purification in the mining area. This study could offer references for the prevention and control of mining water hazards and the protection of water resources in Xinjiang.